SIGN SYSTEM YANG INTEGRAL STUDI KASUS: KAMPUS B, UNIVERSITAS TRISAKTI JAKARTA - Bambang Tri Wardoyo (ULTIMART Jurnal Komunikasi Visual, 2019)
The grammar of visual design plays an equally vital role in the production of meaning. This article uses a number of examples of sign systems at Trisakti University, Medical Dental Faculty, campus B, for an easy understanding. The aim of this article also to analyze how the sign systems are used to produce meaning by contemporary image-makers. This provides a systematic and comprehensive account of the grammar of visual design. Looking at the formal elements and structures of design such as colors, texts, framing, and compositions, this article examines the ways in which images communicate meaning. The findings from this article are essential for anyone interested in design, communication, media, and art.